Perspektif Zakî Najîb Mahmûd tentang Ilmu dan Agama dalam Logika Positivisme - Ghozi, Ghozi (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2011)
This article aims at comprehensively examining Zakî Najîb Mahmûd?s thought on the logic of positivism on the relationship between religion and science. The study employs literature interpretation method. The study encompasses the logic of positivism of Zakî Najîb Mahmûd, confirmation map of knowledge on areas of science and religion, and the dichotomy of science and religion. The study finds that the logic of positivism formulated by Zakî Najîb Mahmûd has accommodated religious knowledge as a scientific matter just like positive science in which its references can be mapped out through accountable epistemological aspect.